Interactions among a Fimbrin, a Capping Protein, and an Actin-depolymerizing Factor in Organization of the Fission Yeast Actin Cytoskeleton - Nakano, Kentaro (The American Society for Cell Biology, 2001)
We report studies of the fission yeast fimbrin-like protein Fim1, which contains two EF-hand domains and two actin-binding domains (ABD1 and ABD2). Fim1 is a component of both F-actin patches and the F-actin ring, but not of F-actin cables. Fim1 cross-links F-actin in vitro, but a Fim1 protein lacking either EF-hand domains (Fim1A12) or both the EF-hand domains and ABD1 (Fim1A2) has no actin cross-linking activity. Overexpression of Fim1 induced the formation of F-actin patches throughout the cell cortex, whereas the F-actin patches disappear in cells overexpressing Fim1A12 or Fim1A2. Thus, the actin cross-linking activity of Fim1 is probably important for the formation of F-actin patches. The overexpression of Fim1 also excluded the actin-depolymerizing factor Adf1 from the F-actin patches and inhibited the turnover of actin in these structures. Thus, Fim1 may function in stabilizing the F-actin patches. We also isolated the gene encoding Acp1, a subunit of the heterodimeric F-actin capping protein. fim1 acp1 double null cells showed more severe defects in the organization of the actin cytoskeleton than those seen in each single mutant. Thus, Fim1 and Acp1 may function in a similar manner in the organization of the actin cytoskeleton. Finally, genetic studies suggested that Fim1 may function in cytokinesis in cooperation with Cdc15 (PSTPIP) and Rng2 (IQGAP), respectively.